Faktor-faktor Yang Mempengaruhi Penyusunan Anggaran Berbasis Kinerja di Pemerintah Provinsi Gorontalo - Hasan, Wahyudin (Gorontalo Accounting Journal, 2018)
This study aims to describe the factors that influence the performance-based budgeting Gorontalo provincial government by using descriptive research method approach. As for the background of this research is with the issuance of Law No. 17 of 2003 on State Finance which includes a variety of fundamental changes in the approach to budgeting. Such changes would require the support system that is more responsive budgeting, which could facilitate efforts to meet society's demands for improved government performance in the areas of development, quality of service and efficiency of resource utilization.Seeing the conditions in local and central government and supported by the applicable rules then it should budgeting system in Indonesia is still input-based budgeting system was replaced with that is able to respond to those changes. In its place is the State Budget Based on Job Performance or term that is more commonly used is the Performance-Based Budgeting. The process of drafting and targets to be achieved from performance-based budgeting system illustrates the opportunity for the regions to develop vision and mission and realize the wishes and expectations of society in accordance with the potential of the area in question.